Contentment as a dimension of human character: with special reference to Bediuzzaman Sa’id Nursi’s Risale-I Nur - Ali, Mohammed Farid (2012)
This paper looks at contentment (qana'ah) in Risale-i Nur of Sa’id Nursi. Nursi described the virtue of contentment by highlighting its opposite which is greed (hirs). He advances the thesis that greed is the source of destruction, whereas contentment is the means to mercy and beneficence. Nursi referred to Qur’anic verses and hadith and gave illustrations and allegories to express his views on contentment. Nursi’s approach to contentment and greed is not limited to personal character only, but highlights its significance to social well-being and to the practicalities of life, the realities of our time and the good advice it can provide for today’s generation, oil producing countries, and the industrial West. Contentment is also important for human character building and plays a role in the larger agenda of Islah and localisation renewal. Nursi’s work stands out for its insightful contribution to the relationship of character, self-discipline, and qana'ah with the rise and fall of societies and civilisations.